FORMULATING KRI MARITIME SECURITY CAPABILITY USING FUZZY WEIGHTING - Bill Saudiaz; Didit Herdiawan; Adi Bandono (JOURNAL ASRO, 2019)
KRI or Indonesian Navy warships has very significant role in maintain the maritime security and uphold the law on Indonesian waters. In order to deploy their KRI, TNI AL needs to measure their KRI Maritime Security (KAMLA) capability. This paper aim is to provide a formula that express KAMLA capability of a KRI out of 3 criterions (sensors, weaponry & Platforms) and 9 sub criterions. Fuzzy Weighting method has been used to derived 4 expert preference into formula of criterion weight. The result is KC = 0,45 S + 0,23 W + 0,32 P. Further work still need to do develop the formula into more detailed criterion.Keywords: KRI, Maritime Security, Fuzzy Weighting